Multipurpose Robot for Automated Cycle Sequencing. (March 2003) - Sawakami-Kobayashi, K.; Segawa, O.; Obata, K.; Hornes, E.; Yohda, M.; Tajima, H.; Machida, M.
Paramagnetic beads have the superior advantages of easy separation and resuspension by controlling the magnetic filed. Previously, we have developed Magtration technology to automate paramagnetic bead handling and have built several automated instruments that handle 1–12 samples simultaneously. To achieve more high-throughput sample processing, two types of a 96-arrayed Integrated Magtration Unit (IMU) were developed, one installed with electromagnets and the other with thin rod-shaped magnets made of neodymium. A multipurpose robot (SX-96GC) equipped with the IMU was also developed for fully automatic processing of 96 samples in parallel. The cleanup of dye-terminator sequencing products was performed using the robot installed with the permanent magnet version of IMU. The results had quality comparable to those by the same protocol in manual handling or to those by the conventional protocols. The robot processed 96 samples in a microplate within 30 min. The protocol that can purify 384 samples within 1 h by processing two microplates concurrently was successfully designed.